The current implementation status of the integration of sports and physical activity into Dutch rehabilitation care. Issue 2 (16th January 2017) - Hoekstra, Femke; Hettinga, Florentina J.; Alingh, Rolinde A.; Duijf, Marjo; Dekker, Rienk; van der Woude, Lucas H. V.; van der Schans, Cees P.
Abstract: Purpose : To describe the current status of the nationwide implementation process of a sports and physical activity stimulation programme to gain insight into how sports and physical activity were integrated into Dutch rehabilitation care. Methods : The current implementation status of a sports and physical activity stimulation programme in 12 rehabilitation centres and 5 hospitals with a rehabilitation department was described by scoring fidelity and satisfaction. Seventy-one rehabilitation professionals filled out a questionnaire on how sports and physical activity, including stimulation activities, were implemented into rehabilitation care. Total fidelity scores (in %) were calculated for each organization. Professionals' satisfaction was rated on a scale from 1 to 10. Results : In most organizations sports and physical activity were to some extent integrated during and after rehabilitation (fidelity scores: median = 54%, IQR = 23%). Physical activity stimulation was not always embedded as standard component of a rehabilitation treatment. Professionals' satisfaction rated a median value of 8.0 (IQR = 0.0) indicating high satisfaction rates. Conclusions : The fidelity outcome showed that activities to stimulate sports and physical activity during and after rehabilitation were integrated into rehabilitation care, but not always delivered as standardized component. These findings have emphasized the importance to focus on integrating these activities into routines of organizations. Implications for Rehabilitation: Components of an evidence-based programme to stimulate sports and physical activity during and after rehabilitation can be used to measure the current status of the integration of sports and physical activity in rehabilitation care in a structural and effective way. The method described in the current study can be used to compare the content of the rehabilitation care regarding the integration of sports and physical activity among organizations both on a national and international level. Sports and physical activity are seen as important ingredients for successful rehabilitation care in The Netherlands.